Job Satisfaction, and Working Environment: Mediating Role of Work-Life Balance - Izharuddin, Muhammad (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study addresses the growing concern of achieving work-life balance and its impact on employee productivity and job satisfaction in various industries. Focusing on the psychological mechanisms, the research explores the mediating role of work-life balance in the association between job satisfaction and work environment. Employing a data mining strategy, the study extracts employee ratings from Jobstreet.com, to compile a sample of 124 companies across diverse industries, providing a quantitative contribution to the emerging field. The research demonstrates the advantages of using social media data to evaluate employer brands, highlighting the inclusive nature of platforms like Jobstreet for diverse user engagement. The research identifies a robust correlation between a healthy work-life balance and improved job performance, emphasizing the need for a deeper understanding of the processes involved. It explores the influence of workplace culture and environment on work-life balance and productivity, particularly how employee satisfaction with coworkers contributes to psychological well-being. The study aims to shed light on how work-life balance mediates the relationship between the work environment and job satisfaction.